Pengaruh Strategi Pembelajaran Course Review Horay Terhadap Hasil Belajar Matematika Siswa di Kelas VII SMP Negeri 15 Baubau - Sardin Sardin; Nuryati La Basi (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2021)
The objective of this study was to determine the effect of the Course Review Horay learning strategy on student mathematics learning outcomes in grade VII at SMP Negeri 15 Baubau.This study was a Quasi-Experiment study. The implementation of the Course Review Horay learning strategy was randomized or selected by randomsampling technique. The population in this study was all grade VII students of SMP Negeri 15 Baubau whuch consisted of 2 classes. Population as well sample, the selected sample in this study was class VII A as the experimental class as many as 17 students and class B as the control class as many as 17 students. The data collection technique in this study was a test and data analysis process used the t test.The results of calculations used the t test obtained =2.352. For the t tabel value at the significance level of 0.05 (5%) and df=32, namely 1.693. Based on these results thus the hypothesis was accepted. It could be concnique that there was a significant effect of the Course Review Horay learning strategy on the mathematics learning outcomes of student in gradeVII at SMP Negeri 15 Baubau.